The influence of changes in intestinal microbiota on the course of inflammatory intestinal diseases - O. V. Gaus; V. A. Akhmedov (Лечащий Врач)
An important role in the development and progression of inflammatory bowel diseases belongs to environmental factors, in particular, the intestinal microbiota. Advances in the technology of genomic sequencing made it possible to establish that it is the change in the composition of the intestinal microbiota that triggers the inflammation in the intestine, and not vice versa, as it was previously thought.